Urgensi Penambahan Kewenangan Profesi Pengamanan Polri Terhadap Penanganan Personil Polri Sebagai Pelaku Tindak Pidana - Iman Azahari Ginting; Syafruddin Kalo; Muhammad Hamdan; Mahmud Mulyadi (USU LAW JOURNAL, 2019)
Abstract. Divpropam was given the authority to deal with the issue of police members who commit criminal acts, if the case is already in question. The Divpropam handlers against the police who commit the crime are limited to the initial examination in accordance with article 5 letter (d) Item (2) Regulation of the Head of the Republic of Indonesia No. 14 Year 2011 concerning profession Ethics Code Indonesian national Police. The research methods used in this research are descriptive analytical, data analysis used in the legal materials in this research will be conducted in a qualitative and comprehensive analytical to primary data and Secondary, this type of research is normative legal research, the collection of data used in this research is covering the literature research (Library Research). In addition to completing secondary data, it is also supported with primary data. Enforcement arrangements against police members who commit a discipline offence are governed by the Government regulation No. 2 year 2003 on disciplinary regulations for police members. Enforcement arrangements against police members who commit violations of the code are set in Law No. 2 of 2002 about the National Police of the Republic of Indonesia which mandated the setting of the Indonesian National Police Profession Code of ethics . The setting of enforcement of police members who commit criminal acts is governed by the legislation in which the police members commit criminal acts. The report or complaint can be done through the function of Reserse and the traffic to handle and examine the alleged police members who have committed a criminal offence, in which case the propam can handle the process after having a permanent law or Through a court ruling. Special code of conduct violations that have to do with criminal acts then for him will be processed in advance in the trial because a police member is heard in the commission of the Code after the Criminal act He did get a permanent law  is stipulated in the Perkap No. 14 year 2011 about the profession of the National Code of Ethics and Perkap No. 19 year 2012 on the organizational arrangement and governance of the Police Code of Ethics Commission of the Republic of Indonesia. Institutional technical for police members. Propam can only perform the next process when the criminal case committed by the police members has been completed the legal and permanent law (fixed legal force) in order to conduct the process of checking the police profession code of ethics in accordance by Perkap No. 14 year 2011 about the code of ethics of the Indonesian professional police and Perkap No. 19 year 2012 on the organizational structure and governance of the National Police Code of Ethics Commission of the Republic of Indonesia.   Keywords:  additional authority, PROPAM, criminal offence